Lobe X of the Cerebellum: A Natural Neuro-Resistant Region - Carlos Hernández-Pérez; Eduardo Weruaga; David Díaz (MDPI AG, 2023)
The cerebellum is an encephalic region classically known for its central role in the control of movement, although recent research has revealed its involvement in other cognitive and affective tasks. Several different pathologies are known to affect this structure, causing a wide range of behavioral and gait impairments. Intriguingly, although the neurodegenerative factors affect all Purkinje cells of the cerebellum uniformly, certain neurodegeneration patterns can be distinguished, in which some Purkinje cells persist longer than other cell types. Specifically, there is a cerebellar region, lobe X, which is more resistant to different types of neurodegeneration, regardless of the injury. Degeneration patterns of the cerebellum have been described in several models, but this review goes further, as it aims at describing a phenomenon not so described: the resistance of the lobe X to neurodegeneration. For this purpose, the main models of cerebellar degeneration will be reviewed and a common origin for the lobe X resistance will be sought.